Hydrophobic mismatch and sequence specificity compete when transmembrane helix-helix interactions are measured with the TOXCAT assay - Hellmann, Nadja; Schneider, Dirk (Frontiers in Chemistry, 2022)
Genetic assays capable of measuring the propensity of transmembrane helices to oligomerize within the cytoplasmic membrane of the bacterium E. coli are frequently used when sequence-specificity in transmembrane helix-helix interactions is investigated. In the present study, dimerization of the well-investigated wild-type and G83I-mutated transmembrane helix of the human glycophorin A protein was studied. Gradual prolongation of the transmembrane helix at the C-terminus with Leu residues lead to pronounced changes in the dimerization propensity when measured with the TOXCAT assay. Thus, besides sequence specificity, hydrophobic mismatch between the hydrophobic core of a studied transmembrane helix and the E. coli membrane can impact the oligomerization propensity of a transmembrane helix. This suggests that the results of genetic assays aiming at determining interactions of heterologous transmembrane helices within the E. coli membrane do not necessarily solely reflect sequence specificity in transmembrane helix-helix interactions, but might be additionally modulated by topological and structural effects caused by hydrophobic mismatch.